2023
DOI: 10.1108/jbsed-11-2022-0121
|View full text |Cite
|
Sign up to set email alerts
|

The impact of applying the target cost and continuous improvement (Kaizen) on achieving the sustainable competitive advantage of Palestinian industrial companies

Abstract: PurposeThis study aims to examine the impact of implementing target costing and continuous improvement techniques in industrial companies operating in southern Palestine on achieving sustainable competitive advantage (SCA). The study mainly assesses the level of application of these techniques by Palestinian industrial companies (PICs). Furthermore, it evaluates the extent to which the integration of these two methods can impact SCA, by producing cost-effective and innovative products that meet customer demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
5
0
2
Order By: Relevance
“…The combination of Kaizen and Target Costing can provide a comprehensive solution for manufacturing companies looking to improve efficiency and competitiveness. This can be supported by a study (Alkababji, 2023) where findings of the study revealed that the integration of Target Costing and continuous improvement had a positive impact on achieving sustainable competitive advantage in Palestinian industrial companies. However, the study found no impact on company size, age, or industrial sector on achieving a competitive advantage in terms of market share or other results.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…The combination of Kaizen and Target Costing can provide a comprehensive solution for manufacturing companies looking to improve efficiency and competitiveness. This can be supported by a study (Alkababji, 2023) where findings of the study revealed that the integration of Target Costing and continuous improvement had a positive impact on achieving sustainable competitive advantage in Palestinian industrial companies. However, the study found no impact on company size, age, or industrial sector on achieving a competitive advantage in terms of market share or other results.…”
Section: Discussionmentioning
confidence: 66%
“…A company can avoid larger problems from arising and keep the production process running smoothly by identifying and addressing small issues as they arise. This can be justified by the fact that the more the company's management practices continuous improvement, the more effectively it can address defects, resulting in development and creativity and, eventually, sustainable competitive advantage for the establishment (Alkababji, 2023) Target Costing, on the other hand, is a cost management methodology that sets a target cost for a product based on customer needs and competitive pricing by focusing on the primary cost drivers in the manufacturing process. By implementing Target Costing, manufacturing businesses can design products that meet customer needs while remaining cost-effective, allowing them to compete in a highly competitive market.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations